Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.3171/jns.1999.90.1.0160
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of true frameless stereotaxy: in vivo measurement and laboratory phantom studies

Abstract: The authors present the results of accuracy measurements, obtained in both laboratory phantom studies and an in vivo assessment, for a technique of frameless stereotaxy. An instrument holder was developed to facilitate stereotactic guidance and enable introduction of frameless methods to traditional frame-based procedures. The accuracy of frameless stereotaxy was assessed for images acquired using 0.5-tesla or 1.5-tesla magnetic resonance (MR) imaging or 2-mm axial, 3-mm axial, or 3-mm helical computerized tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 26 publications
(25 reference statements)
8
107
0
Order By: Relevance
“…Dorward et al [27] found a euclidean error of 4.8 mm in the in vivo arm of their study. Mascott et al [26] report mean localization errors between 3.3 and 5.4 mm.…”
Section: Frameless Stereotaxy: a Hypothetical Cohortmentioning
confidence: 79%
See 1 more Smart Citation
“…Dorward et al [27] found a euclidean error of 4.8 mm in the in vivo arm of their study. Mascott et al [26] report mean localization errors between 3.3 and 5.4 mm.…”
Section: Frameless Stereotaxy: a Hypothetical Cohortmentioning
confidence: 79%
“…Studies using phantom models typically measure the mean error of localization, which represents the average magnitude of the distance between the probe and its intended target. This should not be confused with the mean errors reported for individual axes in some in vivo [27] and phantom [28] studies which utilized planar imaging to measure targeting accuracy. In such instances mean errors refers to the average error within a single anatomic plane.…”
Section: Frameless Stereotaxy: a Hypothetical Cohortmentioning
confidence: 99%
“…The accuracy of the present method is comparable to those of both frame-based and frameless stereotaxy methods. 2,3,22) Review of the largest published series of 7471 stereotactic brain biopsies found the average diagnostic yield was 91% (80-99%), the mortality was 0.7% (0.5-2.6%), and the morbidity was 3.5% (0-13%). 8) In our series, none of the biopsy samples yielded normal brain tissue, and a final histological diagnosis was obtained in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The frameless stereotaxy technique can eliminate the cumbersome head frames, including the time for application, and achieved an accuracy comparable to frame-based stereotaxy. 1,3,4,14,22) Intraoperative magnetic resonance (iMR) imaging and MR-compatible devices have been developed for stereotactic procedures. Two different approaches to the clinical application of iMR imaging have been reported: low-field iMR imaging for stereotactic procedures because of the easy access to patients due to the open configuration, 2,16,25,26) and high-field MR imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the chosen experimental approach allows us to separately evaluate the imaging contribution and the global accuracy, while in the literature, with few exceptions (Kaus et al 1997, Torresin et al 1999, only the latter one is normally investigated (Dorward et al 1999, Vannier and Haller 1999, Zylka et al 1999, Maciunas et al 1994, Willems et al 2001. …”
Section: Introductionmentioning
confidence: 99%